Unveiling the rivalry of cloud ERP dialectics, underpinning logics and roles of accounting and information system professionals - Sameh Farhat Ammar (22303885) (2025)
This study delves into the dialectical implications of Cloud-ERP within organisations, emphasising the roles of accountants and information systems (IS) professionals across various organisational sizes. Adopting an institutional logic perspective, it explores the multiplicity, contestation, and mechanisms that elucidate the hybridity nature of Cloud-ERP and its impact on organisations and the involvement of accountants and IS professionals. The study employs semi-structured interviews, observations and organisational archives. Data analysis was conducted through NVivo Plus, identifying fundamental dialectics and the prominence of various institutional logics within implicated organisations and mobilising different professionals and mechanisms to manage these implications effectively. We identified two primary competing logics—business and technical—manifesting in Cloud-ERP instantiated by three pairs of interactable dialectics: economisation vs transparency, accessibility vs restriction, and efficiency vs misalignment. The importance of these dialectics varies across organisational sizes: transparency in large organisations, accessibility in medium-sized enterprises, and misalignment in small enterprises. This dynamic interplay, influenced by the roles of accountants and IS professionals, highlights the need for context-specific collaborative mechanisms, practical in large organisations, trust-based in medium enterprises, and pragmatic in small enterprises, to manage these competing logics effectively. The findings have implications for theory and practice, providing insights into the dialectics, tension, and complex decision-making landscape of Cloud-ERP. Other Information Published in: International Journal of Accounting Information Systems License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.accinf.2025.100728